Excellence Class Program Management InnovationCase Study on MTs Negeri Kota Tegal (International Journal of Scientific Research and Management (IJSRM), 2024)
Education is one of the most important aspects of human life. With education, human life will become directed towards a better goal. However, the progress of an education is also largely determined by the management of the institution itself. To manage educational institutions towards a more advanced direction, effective management innovation is needed. As done at MTs Negeri Kota Tegal, by implementing superior class program management innovations to improve the quality of education. From the research conducted, MTs Negeri 1 Tegal has carried out innovative management of the upper class program. This application has succeeded in improving the quality of education in institutions, especially those related to student achievement.